Effectiveness Long Time Immersion Sangkuriang Catfish Eggs in Flower Extract Kecombrang for Prevention Fungus Saprolegnia Sp - Rosidah Rosidah; Yuli Andriani; Walim Lili; Irfan Herdiawan (JURNAL PERIKANAN DAN KELAUTAN, 2017)
Fry availability is an important factor in the cultivation of Sangkuriang catfish. Continuity of fry availability is determined by the number of hatching eggs. The low of hatching rate mainly caused by the Saprolegnia sp. attack. One attempt to overcome the Saprolegnia sp. attack on fish eggs is by using Kecombrang flowers (Nicolia speciosa Horan). Anti-fungal compounds contained in Kecombrang flower was phenol, tannin, alkaloids, and flavonoids. The aim of this research is to find the immersion duration of Sangkuriang catfish eggs in the extract of Kecombrang flower most effectively to prevent the attack of Saprolegnia sp. and increase the egg hatching rate. The method in this study was Completely Randomized Design (RAL) experimental method with five treatments and three replications. The treatments was time of immerse the eggs of Sangkuriang catfish in Kecombrang flower extract at 60 ppm for 10, 15, 20, 25 minutes and without immersion as control. The investigate parameters in this study were Saprolegnia attack rate and hatching rate. Results of the experimental analyzed by F test, and if it was a significance difference then continue with Duncan Multiple Range Test at the 5% level. The results showed that the 20 minutes of immersion duration resulted in the lowest Saprolegnia attack rate about 13.50% and the highest egg hatching rate about 72.50%.